Can Urban Design Foster Greater Inclusivity for Women in Public Spaces? - Benny, Nimmy; R, Sharat Sunder; K, Prajitha T; Kini, Manoj Kumar (Journal of Contemporary Urban Affairs, 2024)
As urbanization accelerates globally, creating inclusive public spaces that accommodate women's rights and freedoms becomes increasingly vital. This study critically assesses the impact of urban environments on women in public spaces within the Indian context, focusing on Marine Drive in Kochi, Kerala. Employing field investigations, mapping, and both qualitative and quantitative analyses—including surveys of 100 women—the research explores elements affecting women's quality of life in urban settings. Key factors identified include safety concerns, inadequate accessibility, and insufficient infrastructure that hinder women's equitable participation in public spaces. Literature reviews and case studies highlighted parameters influencing women's experiences, such as land use, mobility, visibility, and safety. A theoretical framework addressing design, physical, environmental, cultural, and economic aspects was developed to create gender-sensitive urban spaces. Applying this framework to the design element of land led to specific guidelines enhancing accessibility, mobility, and permeability, which are crucial for women's comfort and security. The findings contribute to a deeper understanding of women's interactions with urban environments and provide a foundation for urban planners and policymakers to develop women-friendly public spaces, thereby promoting inclusivity and enhancing the overall urban experience.